A preliminary evaluative study of the ElCIA: Integrated Information Audit framework for electricity companies - Shariff S.S.M.; Ariffin I.; Latif A.A.; Nadzir M.M. (2023)
The importance of information as a strategic organisational asset has been highlighted by researchers in a number of studies. Many large organisations especially those in utility industry realize that it is crucial to ensure that the 'right' information is always available when strategic decisions need to be executed. Based on the literatures reviewed on this subject matter, it can be observed that currently the number of frameworks available to help such organisation assess the quality of the information they possess is still limited. This is especially true for electricity companies. One attempt to fill up this gap was done in 2008 in which a specifically tailored Information Audit framework to electricity companies was introduced, known as ElCIA framework. This paper will evaluate the formulated ElCIA framework by identifying its strengths and weaknesses. This identification is an initial step for a study designed to provide further recommendation on how the framework can be enhanced for a much easier adoption by electricity companies. 2013 IEEE.